Entrepreneurial Finance Governance on SMEs: A Bibliometric Co-Authorship Analysis - Erna Maulina; Margo Purnomo; Yogi Sugiarto Maulana; Agus Taryana; Ahmad Hadi Fauzi; Francisco Carballo (Journal of Governance, 2023)
This article aims to find out the development of the government's role in providing SME financial governance policies. The development of knowledge is seen from the relationship and direction of collaboration of affiliation, country, and relationship between authors so that the dynamics of novelty can be known. The method used is bibliometric science mapping. Data was taken from the Scopus database in several stages, namely identification, filtering (inclusion and exclusion criteria), and data finalization. We use the Analyse Results and Source menus on Scopus, Scimago Journal, and Country Rank. Cluster co-authorship calculations and their visualisations use VOSviewer software version 1.6.12. The results showed that publications on the topic of entrepreneurial finance began to appear in 1992. The United States was the country with the most publications, with an output of 92 documents out of a total of 327 documents. The most prolific writer is Douglas Cumming, with a total of 18 articles. Based on the visualisation analysis of VOSviewer, Douglas Cumming has a strong relationship in terms of collaborative writing with Silvio Vismara, Massimo G. Colombo, and Joern Block. The results of his research found that venture capital was approached significantly by technology-based companies compared to other external sources of capital. The results of our mapping can be used to determine reference information and future research bases, both by author and by country, for the application and development of the topic of entrepreneurial finance research, especially for SMEs.